Experience of prehospital emergency care among general practitioners in Ireland. Issue 7 (23rd June 2008) - Bury, G; Prunty, H; Egan, M; Sharpe, B
Abstract : Background: Although widely acknowledged, few data exist on the scope of general practice involvement in the management of prehospital emergencies. A study was undertaken to explore the frequency and types of emergencies dealt with and the interventions undertaken by GPs who had completed Immediate Care training. Methods: All participants in Immediate Care courses in Ireland in 2002, 2003 and 2004 were invited to complete an anonymised questionnaire in which they estimated their experience of emergencies since completing a course. Sections dealt with personal/practice information, types of emergencies, interventions used and follow-up training. Results: 448 participants completed courses, 408 were available to participate in the study and 259 (63.5%) responded; 66.6% of GPs responded. The mean reporting period was 29.4 months (range 18–53). Participants included many younger female GPs at the start of their general practice careers. Although most emergencies dealt with were medical, few other patterns emerged in the timing or setting of emergencies. 88% of GPs had called an ambulance in an emergency at least once in the preceding year. 84% of GPs had managed a suspected acute myocardial infarction at least once during the reporting period; seizures, serious injuries, paediatric emergencies and hypoglycaemia were dealt with by up to half of all GPs. Interventions used included intravenous access in a medical emergency (69%), intravenous fluid administration (51%), intravenous morphine (54%), cardiopulmonary resuscitation (37%), defibrillation (21%), use of airway adjuncts (28%) and use of advanced life support drugs in cardiac arrest (24%). Conclusions: GPs make frequent use of a wide range of interventions in prehospital emergencies. Issues relating to tailored training, adequate equipment, collaboration with the emergency services and skills maintenance are highlighted by these data.